Host competence of Algerian Gerbillus amoenus for Leishmania major - Benallal, Kamal Eddine; Mezai, Ghania; Mefissel, Mohammed; Klari, Nadia; Lardjane, Cylia; Khardine, Ahmed-Fayez; Kherachi, Ihcen; Dib, Yacine; Brahmi, Karima; Sadlova, Jovana; Volf, Petr; Harrat, Zoubir (International journal for parasitology. Parasites and wildlife, 2023)
Cutaneous leishmaniasis (CL) is the most important neglected disease reported in North Africa, Algeria ranks second in the world with more than 5000 cases per year. In Algeria, two rodent species Psammomys obesus and Meriones shawi, are so far known as proven reservoirs of Leishmania major, however, they are absent in several endemic localities. In this study, we experimentally infected Gerbillus rodents trapped around human dwellings in Illizi, Algeria to assess their susceptibility to L. major. Seven gerbils, morphologically and molecularly identified as Gerbillus amoenus, were intradermally inoculated with 104 parasites derived from culture, monitored for six months and their infectiousness for sand flies was tested by xenodiagnosis. The study revealed that G. amoenus was susceptible to L. major and was able to maintain and transmit the parasites to sand flies tested six months after infection, suggesting the role of this gerbil as a potential reservoir for L. major.
Keywords: Algeria; qPCR; Leishmaniasis; Rodents; Leishmania major; Gerbillus amoenus; Xenodiagnostic